Correlation Between Visual Field Sensitivity and Retinal Nerve Fiber Layer Thickness in Unilateral Exfoliation Syndrome - Marija Šimić Prskalo; Zrinko Prskalo; Željka Tomić; Teo Tomić (Acta Clinica Croatica)
This study aimed to evaluate retinal nerve fiber layer thickness in exfoliation syndrome (XFS), present unilaterally, using optical coherence tomography (OCT). This prospective study included 90 examinees with unilateral syndrome. However, examinees with higher intraocular pressure or findings implicative of glaucoma were excluded from the study, as well as examinees with optic nerve changes. In individuals with unilateral XFS, OCT findings were compared between the two groups: the affected eye group and the fellow eye group. The study results show that the average thinning of the retinal nerve fiber layer, especially in the inferior and superior quadrants, has not resulted in visual field defects in examinees with unilateral XFS. In the group of eyes without XFS, 85.55% exhibited reference inferior quadrant thickness values, and 91.11% exhibited reference superior quadrant thickness values. In the group of eyes with manifest XFS, 82.22% exhibited reference inferior quadrant thickness values, and 88.88% exhibited reference superior quadrant thickness values. Most examinees in both groups had normal average retinal nerve fiber layer (RNFL) thickness (72.22%). In examinees with clinically unilateral XFS, RNFL thinning occurs in both eyes before XFS becomes bilateral and before hypertensive intraocular pressure can be measured.